Storytelling to immersive learners in an authentic virtual training environment - Wood, L.; Reiners, Torsten (2015)
Education and assessment activities within the university environment are still frequently bounded by classroom walls and lack of authenticity; i.e., when we examine the skills required by graduates. We explain how the project nDiVE addresses these issues by immersing the learners in a virtual environment and getting them included in a storyline. Gamification elements are used to increase the engagement with the environment and focus attention on the tasks at hand, involving learners’ curiosity and sense of adventure to increase self-directed learning. Authentic assessment tasks can be designed to provide formative feedback and aid the learners as they progress their understanding of the discipline. As the nDiVE project is ongoing, we highlight some additional areas where further investigation is still in progress, emphasising the need to understand how particular gamification mechanisms relate to intrinsic motivation, and present first experimental findings using a self-exploratory scenario.